The answer is:
![k=-1](https://img.qammunity.org/2019/formulas/mathematics/middle-school/eecsahmdh343qk5690wdy3jiihhe9uxpv7.png)
The explanation is shown below:
1. By the exponents properties, when you have equal bases, you must sum the exponents of all the bases.
2. Based on this, let's write only the exponents and let's solve for
to calculate its value:
![-3+1+k=-3\\ k=-3+3-1\\ k=-1](https://img.qammunity.org/2019/formulas/mathematics/middle-school/fvctwo2lvrszgaiq8r62s376v0yfngqdcf.png)
Therefore, the answer is
![k=-1](https://img.qammunity.org/2019/formulas/mathematics/middle-school/eecsahmdh343qk5690wdy3jiihhe9uxpv7.png)